Shirley Backstrom - (Interviewer); Shirley Backstrom (Interviewee) (2019)
Born and raised in Amber Valley and Edmonton, AB. Spent 34 years in the North West Territories. Raising her 6 children, 2 of whom were adopted as infants in the NWT, she devoted herself to volunteering with activities surrounding family, faith, youth and community life: music, sports and arts & crafts. She continues to do so across the areas of: Athabasca, Colinton and Amber Valley. She is a proud member of the Royal Purple, Colinton Seniors and Athabasca Native Friendship Centre.